The diary of Virginia Woolf - Woolf, Virginia frey50; Bell, Anne Olivier (Harcourt Brace Jovanovich New York, 1977)
v. 1. 1915-1919 -- v. 2. 1920-1924 -- v. 3. 1925-1930 -- v. 4. 1931-1935 -- v. 5. 1936-1941.
Editor's preface and acknowledgments 1920 1921 1922 1923 1924 Abbreviations Appendix I: Biographical outlines Appendix II: "The plumage Bill" Appendix III: "The intellectual status of women" Index
Includes bibliographical referenes and index.
Keywords: Woolf, Virginia -- 1882-1941 -- Diaries; Women novelists, English -- Diaries. -- 20th century